When Speech Stops, Gesture Stops: Evidence From Developmental and Crosslinguistic Comparisons - Graziano, Maria; Gullberg, Marianne (Frontiers in Psychology, 2018)
There is plenty of evidence that speech and gesture form a tightly integrated system, as reflected in parallelisms in language production, comprehension, and development (McNeill, 1992; Kendon, 2004). Yet, it is a common assumption that speakers use gestures to compensate for their expressive difficulties, a notion found in developmental studies of both first and second language acquisition, and in theoretical proposals concerning the gesture-speech relationship. If gestures are compensatory, they should mainly occur in disfluent stretches of speech. However, the evidence is sparse and conflicting. This study extends previous studies and tests the putative compensatory role of gestures by comparing the gestural behavior in fluent vs. disfluent stretches of narratives by competent speakers in two languages (Dutch and Italian), and by language learners (children and adult L2 learners). The results reveal that (1) in all groups speakers overwhelmingly produce gestures during fluent speech and only rarely during disfluencies. However, L2 learners are significantly more likely to gesture in disfluency than the other groups; (2) in all groups gestures during disfluencies tend to be holds; (3) in all groups the rare gestures completed in disfluencies have both referential and pragmatic functions. Overall, the data strongly suggest that when speech stops, so does gesture. The findings constitute an important challenge to both gesture and language acquisition theories assuming a mainly (lexical) compensatory role for (referential) gestures. Instead, the results provide strong support for the notion that speech and gestures form an integrated system.